Analysis of Multi Stakeholder Processes in Ecosystem Based Marine Management - A Case study - Raj, James Emmanuel; Hellekant, Josefin (My University, 2022)
Increasing public knowledge in environmental matters and decisions combined with a growing scepticism of science and distrust in management processes has pushed the need for enhanced decision and management methods. The very use of participation has been filled with intrinsic value and meaning, such as social, ideological, methodological and political. Stakeholder participatory processes could help widen perspectives of issues and be put in different contexts, thus increasing the quality of decision-making in environmental management. The study aimed to identify the gaps and places of improvement with an eye to explore and understand the obstacles linked to Multi stakeholder networks. The outcome of the study was aimed to support dialogic dynamics among the involved stakeholders and to contribute to the understanding of how these types of participatory processes can be improved. The study’s focus was directed towards the three pilot projects administered by SwAM that worked towards developing an Ecosystem Based Marine Management model. The methodology of this study involved conducting semi-structured interviews to elicit information from the interviewees. The results were based on the themes of Stakeholder Identification, Perceptions of pilot’s purpose, Expectations, Perceived working climate, Communication channels and Challenges. An analysis was performed respectively by comparing the data obtained with the compiled literature on how a good MSP should work. Upon performing the analysis, common and individual hindrances affecting the process’s effectiveness and productivity were identified among pilots. The overall pulse of the pilot process was understood to be quite good, but it could be tweaked even more by improving certain measures. The pilot’s unique administration and facilitation proved that MSPs could also be performed in such ways where more weightage was placed on ensuring a bottom-up, democratic and inclusive approach.
Keywords: EBMM; Stakeholder; Multi-Stakeholder Process; Bottom-up approach; Challenges; Perspectives; Perceptions; Differences; Attributes for a good MSP